2022
DOI: 10.3389/fonc.2022.906484
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of dose to vascular target volumes and local failure in pancreatic cancer patients undergoing neoadjuvant chemoradiation

Abstract: ObjectiveThe objectives of this study were to evaluate whether dose to the vasculature is associated with local control after surgery in patients with borderline resectable (BLR) and resectable pancreatic cancer (PCA) receiving neoadjuvant radiation therapy (RT) and to identify a dose threshold for clinical use.MethodsPatients with BLR and resectable PCA treated with neoadjuvant RT were retrospectively reviewed. During this period, the institutional paradigm shifted from standard fractionation to hypofractiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Nelson et al analyzed 47 patients with borderline resectable and resectable pancreatic cancer and found that the dose to the vascular CTV defined as a 5-mm margin around the superior mesenteric artery was associated with durability of local control after resection. 34 Patients who had a vascular CTV D95 ≥32.7 Gy EQD2 had significantly longer local failure-free survival at 12 months (91% vs 51%, respectively) and 24 months (86% vs 12%). These findings suggest that there may be a benefit to increasing the radiation treatment volume to encompass some elective nodal coverage and pancreatic vasculature.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Nelson et al analyzed 47 patients with borderline resectable and resectable pancreatic cancer and found that the dose to the vascular CTV defined as a 5-mm margin around the superior mesenteric artery was associated with durability of local control after resection. 34 Patients who had a vascular CTV D95 ≥32.7 Gy EQD2 had significantly longer local failure-free survival at 12 months (91% vs 51%, respectively) and 24 months (86% vs 12%). These findings suggest that there may be a benefit to increasing the radiation treatment volume to encompass some elective nodal coverage and pancreatic vasculature.…”
Section: Discussionmentioning
confidence: 89%
“…Of the 73 patients who underwent definitive resection, 30 experienced a recurrence with site of first recurrence local only in 3%, locoregional in 22%, distant in 44%, and both locoregional and distant in 22%. 22 Additionally, Hill et al 34 recently published a large retrospective series of 155 patients who underwent SBRT to a median dose of 33 Gy for borderline-resectable and locally advanced pancreatic cancer followed by surgical resection. Although the authors found locoregional failures in 33% of patients, local only failures were uncommon (14%) as the first site of progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation